Crystal Structure and Catalytic Activity of Poly[bis(3-bromo-2-hydroxybenzaldehyde)-2-aminopyrimidinemagnesium(II)] for Hydrogenation of 1,3-Butadiene - Li-Hua Wang; Fan-Yuan Kong; Xi-Shi Tai (Bulletin of Chemical Reaction Engineering & Catalysis, 2021)
A new six-coordinated Mn(II) coordination polymer, [Mn(L1)(L2)2]n (L1 = 2-aminopyrimidine, HL2 = 3-bromo-2-hydroxybenzaldehyde) was synthesized by 3-bromo-2-hydroxybenzaldehyde, NaOH, 2-aminopyrimidine and manganese(II) acetate dihydrate. The Mn(II) coordination polymer was structural characterized by elemental analysis and single crystal X-ray diffraction. The results show that each Mn(II) ion is six-coordinated with two phenolic hydroxyl O atoms from two 3-bromo-2-hydroxybenzaldehyde ligands (O1 and O4), two formyl group O atoms from two 3-bromo-2-hydroxybenzaldehyde ligands (O2 and O3), and two N atoms from two 2-aminopyrimidine molecules (N1A and N2), and forms a distorted octahedral coordination geometry. The Mn(II) coordination polymer displays a 1D chained structure by the bridge effect of 2-aminopyrimidine N atoms. The catalytic activities of Mn(II) coordination polymer and Pd@Mn(II) coordination polymer for hydrogenation of 1,3-butadiene have been investigated. The Pd@Mn(II) coordination polymer catalyst shows the good catalytic activity and selectivity in  the hydrogenation of 1,3-butadiene. The 1,3-butadiene conversion is 61.3% at 70 °C, and the selectivity to total butene is close to 100%. Copyright © 2021 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).